Ocean outbreak confronting the rising tide of marine disease - Harvell, C. Drew, 1954- (University of California Press, 2019)
"There is a growing crisis in our oceans as rates of infectious disease outbreaks are on the rise. Marine epidemics have the potential to cause a mass die-off of wildlife from the bottom to the top of the food chain, impacting the health of ocean ecosystems as well as lives on land. Ocean outbreaks are a sentinel of an impending global environmental disaster, fueled by sewage dumping, unregulated aquaculture, and drifting plastic in a warming ocean. Ocean Outbreak follows renowned scientist Drew Harvell and her colleagues as they investigate how four iconic marine animals--corals, abalone, salmon, and starfish--have been devastated by disease. Based on over twenty years of research, this firsthand account of the sometimes creeping, sometimes exploding impact of disease outbreaks on our ocean's biodiversity ends with a hopeful message. Through policy changes and the implementation of innovative solutions from nature, we can reduce major outbreaks, save some ocean ecosystems, and protect our fragile environment"--Provided by publisher.